Banco de dados do programa SIE, módulo biblioteca, com materiais especiais aplicáveis à geomática - Fernandes, Luiz Marchiotti (2008)
This work approaches the organization of aerial images by remote sensor, maps, photos, topographical letters, in the System SIE, module library, of the System of Libraries used in the Federal University of Santa Maria UFSM. Some steps for the inclusion of bibliographical registers are presented and registering item, which those compose the search system, by Internet from the university site. The choice for using a free software as a result from analysis of the four great available programs in the market such as Aleph, Pergamum, Gnuteca and SIE. Those systems available, the SIE, the module library was considered the most appropriate for the purpose in question. The application of the test pilot, carried out through in the Sector Library of the Center of Agricultural Sciences component of the System of Libraries of this related institution. It was confirmed the relevancy for this choice because the results were positive and meaningful. In this way, the System SIE becomes of great value for the information managers. It corresponds to be a useful tool for the dissemination of the information. It is a major importance for all the users in potential of this and other institutions of education.